Intention to Patronise Zakat Institution at Kwara State, Nigeria: An Application of the Decompose Theory of Planned Behaviour - Aishat Abubakar Sahban; Fuadah Johari (Universitas Muhammadiyah Malang, 2021)
Patronage is one of the major problems facing zakat institutions in Nigeria. This study aims to analyze the increased zakat collection by examining which factor can encourage patronage of zakat institution in order to increase zakat collection for proper care of destitute in the state and help zakat managers to understand why they should encourage zakat payers with their behavior to be honest and trusted to manage the Muslims wealth. The quantitative research method was applied, a survey questionnaire was conducted among zakat payers, and potential zakat payers in Kwara state and a total of 314 completed survey questionnaires were collected and subjected to structural equation modeling. This study results revealed that attitude and subjective norms influence the zakat payers’ intention to patronize the zakat institution in Kwara state, Nigeria. This research concluded that attitude and subjective norms have positive effects on the intention of zakat payers to patronize zakat institutions in Kwara State.